The Experimental Validation of a Digital Filter Mathematical Modelling for Nuclear Fuel Vibration Monitoring System - Han Yong; Huang Shiyong; Han MengXuan; Zhao Tao; Wen Guang; Gu Mingfei; Zhang Qi (Journal of Function Spaces)
Aiming at vehicles will produce shocks and vibrations for various reasons in the process of transportation and handling, any shock and vibration that exceeds the regulations would cause damage to the nuclear fuel being transported. In order to monitor and analyze the shock and vibration data scientifically, a monitoring system based on MEMS acceleration sensor technology is developed to measure shocks and vibrations. The measured result involves some noise caused by the sensitivity of the sensor and the electrical noise, and a digital filter mathematical modelling is introduced to reduce noise and improve the measured result accuracy. In order to verify the effectiveness of the device designed in this paper, the device and the high-precision seismic acceleration sensor AC73 are, respectively, used for field tests; the results show that the test precision of the designed device can meet the requirements, and also, the designed shock and vibration monitoring system can record and store the three-axis acceleration, temperature, humidity, pressure, time, and other parameters that exceed the set threshold during nuclear fuel transportation in real time and complete the fuel assembly transportation status assessment and promptly remind the transportation personnel to take safety precautions and treatment measures. Therefore, it can be widely used in the monitoring, recording, and postevent data analysis of the transportation process of important products such as nuclear fuel.